Negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

By adopting a double-layer carbon material structure in a nonaqueous electrolyte secondary battery, the capacity and fast charging and discharging performance of the battery are improved, and the problem of insufficient performance in the prior art is solved.

CN114793478BActive Publication Date: 2024-12-13PANASONIC ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080086484.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-24
Filing Date
2020-12-21
Publication Date
2024-12-13
Estimated Expiration
2040-12-21

AI Technical Summary

Technical Problem

The existing nonaqueous electrolyte secondary batteries have shortcomings in fast charging and discharging performance, especially when they are for vehicle-mounted and power storage purposes, it is difficult to take into account high capacity and fast charging and discharging.

Method used

The two-layer carbon material structure is used as the negative electrode active material, and the first negative electrode mixture layer contains the first carbon material with a true density of 2.1 g/cm3 to 2.3 g/cm3, and the second negative electrode mixture layer contains the true density of 1.5 g/cm3 to ~ The second carbon material of 2.0 g/cm3 has a larger particle void ratio than the first carbon material, and the mass ratio of the two layers is 95:5 to 80:20, which improves the permeability of the electrolyte and lithium ion. Diffusion capability.

Benefits of technology

It achieves high capacity and good fast charging and discharging performance, and improves the overall performance of the battery, especially in the fast charging and discharging process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114793478B_ABST
    Figure CN114793478B_ABST
Patent Text Reader

Abstract

The purpose of the present application is to provide a non-aqueous electrolyte secondary battery with high capacity and good rapid charge and discharge performance. As one embodiment of the present application, a negative electrode for a non-aqueous electrolyte secondary battery comprises: a negative electrode collector, a first negative electrode mixture layer disposed on the surface of the negative electrode collector, and a second negative electrode mixture layer disposed on the surface of the first negative electrode mixture layer. The first negative electrode mixture layer comprises a true density of 2.1 g / cm 3 ~2.3g / cm 3 The first carbon material of the second negative electrode mixture layer comprises a carbon material having a true density of 1.5 g / cm 3 ~2.0g / cm 3 The second carbon material in the second negative electrode mixture layer has a larger interparticle void ratio than the first carbon material in the first negative electrode mixture layer, and a mass ratio of the first negative electrode mixture layer to the second negative electrode mixture layer is 95:5 to 80:20.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a negative electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art

[0002] In order to increase the energy density of non-aqueous electrolyte secondary batteries, high-density graphite is sometimes used as the negative electrode active material. However, when the negative electrode active material is composed only of high-density graphite, there is a problem that the battery capacity decreases due to repeated charge and discharge.

[0003] For example, Patent Documents 1 and 2 disclose methods of suppressing a decrease in battery capacity due to charge and discharge cycles by using a mixed material of graphite and a non-graphite carbon material having a lower true density than graphite as a negative electrode active material.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 7-192724

[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 11-250936 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] However, in addition to high capacity, secondary batteries for vehicle-mounted and power storage applications are also required to be capable of rapid charge and discharge. The methods disclosed in Patent Documents 1 and 2 still have room for improvement in rapid charge and discharge performance.

[0010] Therefore, an object of the present application is to provide a non-aqueous electrolyte secondary battery having a high capacity and good rapid charge and discharge performance.

[0011] Technical solutions to solve problems

[0012] The negative electrode for a nonaqueous electrolyte secondary battery as one embodiment of the present application is characterized by comprising: a negative electrode current collector, a first negative electrode mixture layer disposed on the surface of the negative electrode current collector, and a second negative electrode mixture layer disposed on the surface of the first negative electrode mixture layer. The first negative electrode mixture layer comprises a 3 ~2.3g / cm 3 The first carbon material of the second negative electrode mixture layer comprises a carbon material having a true density of 1.5 g / cm 3 ~2.0g / cm 3The second carbon material in the second negative electrode mixture layer has a larger interparticle void ratio than the first carbon material in the first negative electrode mixture layer, and a mass ratio of the first negative electrode mixture layer to the second negative electrode mixture layer is 95:5 to 80:20.

[0013] A nonaqueous electrolyte secondary battery as one embodiment of the present application is characterized by comprising: the above-mentioned negative electrode for the nonaqueous electrolyte secondary battery, a positive electrode, and a nonaqueous electrolyte.

[0014] Effects of the Invention

[0015] According to one embodiment of the present application, a nonaqueous electrolyte secondary battery having a high capacity and excellent rapid charge and discharge performance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a longitudinal cross-sectional view of a cylindrical secondary battery as an example of an embodiment.

[0017] Figure 2 It is a cross-sectional view of a negative electrode as an example of an embodiment. DETAILED DESCRIPTION

[0018] The negative electrode for a nonaqueous electrolyte secondary battery as one embodiment of the present application is characterized by comprising: a negative electrode current collector, a first negative electrode mixture layer disposed on the surface of the negative electrode current collector, and a second negative electrode mixture layer disposed on the surface of the first negative electrode mixture layer. The first negative electrode mixture layer comprises a 3 ~2.3g / cm 3 The first carbon material of the second negative electrode mixture layer comprises a carbon material having a true density of 1.5 g / cm 3 ~2.0g / cm 3 The second carbon material in the second negative electrode mixture layer has a larger interparticle void ratio than the first carbon material in the first negative electrode mixture layer, and a mass ratio of the first negative electrode mixture layer to the second negative electrode mixture layer is 95:5 to 80:20.

[0019] Hereinafter, an example of an embodiment of a cylindrical secondary battery involved in the present application is described in detail with reference to the accompanying drawings. In the following description, specific shapes, materials, numerical values, directions, etc. are examples for making the present invention easy to understand, and can be appropriately changed according to the specifications of the cylindrical secondary battery. In addition, the outer casing is not limited to a cylindrical shape, and can also be, for example, square. In addition, in the following description, in the case of including multiple embodiments and variations, it is initially envisaged that these characteristic parts will be appropriately combined and used.

[0020] Figure 1 It is a longitudinal cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. Figure 1 In the secondary battery 10 shown, the electrode body 14 and the nonaqueous electrolyte (not shown) are accommodated in the outer body 15. The electrode body 14 has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound with the separator 13 interposed therebetween. It should be noted that, in the following, for the sake of convenience, the sealing body 16 side is set as "upper" and the bottom side of the outer body 15 is set as "lower".

[0021] The open end of the outer body 15 is blocked by the sealing body 16, thereby the interior of the secondary battery 10 is sealed. Insulating plates 17 and 18 are respectively provided above and below the electrode body 14. The positive lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the lower surface of the filter 22 which is the bottom plate of the sealing body 16. In the secondary battery 10, the cover 26 which is the top plate of the sealing body 16 electrically connected to the filter 22 becomes the positive terminal. On the other hand, the negative lead 20 passes through the through hole of the insulating plate 18 and extends to the bottom side of the outer body 15, and is welded to the bottom inner surface of the outer body 15. In the secondary battery 10, the outer body 15 becomes the negative terminal. It should be noted that when the negative lead 20 is provided at the terminal portion, the negative lead 20 passes through the outside of the insulating plate 18 and extends to the bottom side of the outer body 15, and is welded to the bottom inner surface of the outer body 15.

[0022] The outer body 15 is, for example, a metal outer can in a cylindrical shape with a bottom. A gasket 27 is provided between the outer body 15 and the sealing body 16 to ensure the airtightness of the interior of the secondary battery 10. The outer body 15 has, for example, a groove portion 21 formed by pressurizing the side surface from the outside to support the sealing body 16. The groove portion 21 is preferably formed in an annular shape along the circumferential direction of the outer body 15, and the sealing body 16 is supported on it by the gasket 27.

[0023] The sealing body 16 has a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cover 26 stacked in order from the electrode body 14 side. The components constituting the sealing body 16 have, for example, a disc shape or a ring shape, and the components except the insulating member 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective central portions, and an insulating member 24 is sandwiched between their respective peripheral portions. If the internal pressure of the battery rises due to abnormal heat, for example, the lower valve body 23 breaks, whereby the upper valve body 25 expands toward the cover 26 side and moves away from the lower valve body 23, thereby cutting off the electrical connection between the two. If the internal pressure rises further, the upper valve body 25 breaks, and the gas is discharged from the opening 26a of the cover 26.

[0024] The following describes in detail the structure of the positive electrode 11, the negative electrode 12, the separator 13 and the non-aqueous electrolyte that constitute the secondary battery 10, especially the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b that constitute the negative electrode 12 (hereinafter, the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b are sometimes collectively referred to as the negative electrode mixture layer 32).

[0025] [negative electrode]

[0026] Figure 2 : is a cross-sectional view of a negative electrode 12 as an example of an embodiment. The negative electrode 12 comprises: a negative electrode collector 30, a first negative electrode mixture layer 32a provided on the surface of the negative electrode collector 30, and a second negative electrode mixture layer 32b provided on the surface of the first negative electrode mixture layer 32a. The mass ratio of the first negative electrode mixture layer to the second negative electrode mixture layer is 95:5 to 80:20. When the mass ratio of the second negative electrode mixture layer to the first negative electrode mixture layer is less than 5 / 95, the permeability of the electrolyte is too low and the rapid charge and discharge performance is deteriorated. In addition, when the mass ratio of the second negative electrode mixture layer to the first negative electrode mixture layer exceeds 20 / 80, the battery capacity will decrease.

[0027] The negative electrode current collector 30 is made of, for example, a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface. The thickness of the negative electrode current collector 30 is, for example, 5 μm to 30 μm.

[0028] The first negative electrode mixture layer includes a 3 ~2.3g / cm 3 The first carbon material has a high energy density, and the secondary battery 10 can have a high capacity. Here, the true density refers to the value obtained by dividing the mass by the volume excluding internal voids and pores, and can be measured, for example, by a pycnometer method. The true density of the second carbon material can also be measured in the same manner.

[0029] The first carbon material is, for example, graphite particles. As graphite particles, natural graphite, artificial graphite, etc. can be exemplified. Natural graphite is obtained, for example, by spheroidizing naturally produced flaky graphite and molding it into an appropriate particle size. Artificial graphite is obtained, for example, by using a petroleum or coal-based asphalt material having a specific particle shape as a starting material, calcining it at about 900°C to 1100°C, thereby temporarily removing volatile components, and then calcining it at a high temperature of more than 2500°C. The true density can be controlled by the calcining temperature, time, and starting material.

[0030] The second negative electrode mixture layer includes a 3 ~2.0g / cm 3The second carbon material may be, for example, easily carbonized graphite or difficultly carbonized graphite. The second carbon material is obtained by calcining a petroleum or coal-based asphalt material having a specific particle shape at about 900°C to 1100°C, and is a material having a graphite structure in at least a part of the crystal structure. The true density can be controlled by the calcination temperature, time, and starting raw materials.

[0031] The interparticle porosity of the second carbon material in the second negative electrode mixture layer is greater than the interparticle porosity of the first carbon material in the first negative electrode mixture layer. The specific true density of the second carbon material is 2.1 g / cm 3 ~2.3g / cm 3 The first carbon material is hard, so the shape does not change after compression when forming the negative electrode mixture layer 32, and a large amount of voids remain between the particles according to the particle shape. By increasing the interparticle void ratio, the permeability of the electrolyte is improved, and the diffusion of lithium ions becomes easier during the expansion and contraction of the negative electrode accompanying charge and discharge, so the rapid charge and discharge performance is improved. In this application specification, the interparticle void ratio of the carbon material is a two-dimensional value calculated based on the ratio of the area of ​​the interparticle voids of the carbon material to the cross-sectional area of ​​the negative electrode mixture layer, which can be calculated as follows.

[0032] <Method for measuring interparticle void ratio of carbon material>

[0033] (1) Exposing the cross section of the negative electrode mixture layer. For example, the following method can be used to expose the cross section: a portion of the negative electrode is cut and processed using an ion milling device (for example, IM4000PLUS manufactured by Hitachi High-Tech) to expose the cross section of the negative electrode mixture layer.

[0034] (2) Using a scanning electron microscope, a reflected electron image of the cross section of each of the exposed negative electrode mixture layer of the first negative electrode mixture layer 32 a and the second negative electrode mixture layer 32 b is taken. The magnification for taking the reflected electron image is, for example, 800 times.

[0035] (3) The cross-sectional image obtained as described above is input into a computer and binarized using image analysis software (e.g., ImageJ, manufactured by the National Institutes of Health, U.S.A.) to obtain a binary processed image in which the particle cross-sectional image is converted to black and the voids existing in the particle cross-sectional image are converted to white.

[0036] (4) In the binary processed images of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b, the voids converted to white, the voids inside the particles of the carbon material (pores not connected to the particle surface) and the pores connected to the particle surface of the carbon material with a width of 3 μm or less are set as the interparticle voids of the carbon material, and the area of ​​the interparticle voids of the carbon material is calculated. The interparticle void ratio of the carbon material can be calculated based on the following formula.

[0037] Carbon material interparticle porosity = area of ​​carbon material interparticle gaps / area of ​​negative electrode mixture layer cross section × 100

[0038] (5) The inter-particle porosity of the first carbon material in the first negative electrode mixture layer 32 a and the inter-particle porosity of the second carbon material in the second negative electrode mixture layer 32 b were each calculated as an average value of the above measurements three times.

[0039] Next, a specific method for forming the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b is described. For example, first, a negative electrode active material, a binder, and a solvent such as water, which contain a first carbon material, are mixed to prepare a first negative electrode mixture slurry. In addition, a negative electrode active material, a binder, and a solvent such as water, which contain a second carbon material different from the first carbon material, are mixed to prepare a second negative electrode mixture slurry. Then, the first negative electrode mixture slurry is applied to both sides of the negative electrode collector, and after drying, the second negative electrode mixture slurry is applied to both sides of the coating obtained using the first negative electrode mixture slurry, and dried. Furthermore, the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b are rolled using a calendering roller, thereby forming the negative electrode mixture layer 32. It should be noted that in the above method, the second negative electrode mixture slurry is applied after the first negative electrode mixture slurry is applied and dried, but the second negative electrode mixture slurry may be applied after the first negative electrode mixture slurry is applied and before drying. In addition, the second negative electrode mixture slurry may be applied on the first negative electrode mixture layer 32a after the first negative electrode mixture slurry is applied, dried and rolled.

[0040] At least one of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b may contain Si-based materials. Si-based materials are materials that can reversibly absorb and release lithium ions, and function as negative electrode active materials. As Si-based materials, for example, Si, alloys containing Si, silicon oxides such as SiOx (x is 0.8 to 1.6), etc. can be cited. Si-based materials are negative electrode materials that can increase battery capacity compared to graphite particles. From the perspective of increasing battery capacity and suppressing the reduction of fast charging cycle characteristics, the content of Si-based materials is preferably 1% to 10% by mass, and more preferably 3% to 7% by mass, relative to the mass of the negative electrode active material.

[0041] As other materials that can reversibly absorb and release lithium ions, metals alloyed with lithium such as tin (Sn), or alloys and oxides containing metal elements such as Sn can also be cited. The negative electrode active material can contain the above-mentioned other materials, and the content of the above-mentioned other materials is preferably less than 10% by mass relative to the mass of the negative electrode active material.

[0042] In addition, the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b preferably include a binder, etc. As the binder, for example, fluorine resin, PAN, polyimide resin, acrylic resin, polyolefin resin, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (PAA-Na, PAA-K, etc., and partially neutralized salt), polyvinyl alcohol (PVA), etc. can be cited. They can be used alone or in combination of two or more.

[0043] [positive electrode]

[0044] The positive electrode 11 is composed of, for example, a positive electrode current collector such as a metal foil and a positive electrode mixture layer formed on the positive electrode current collector. The positive electrode current collector can be a foil of a metal such as aluminum that is stable within the potential range of the positive electrode, a film having the metal disposed on the surface, etc. The positive electrode mixture layer includes, for example, a positive electrode active material, a binder, a conductive agent, etc.

[0045] The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent, etc., on a positive electrode current collector, drying the slurry to form a positive electrode mixture layer, and then rolling the positive electrode mixture layer.

[0046] Examples of the positive electrode active material include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. For example, lithium transition metal oxides are Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1- y M y O z , Li x Mn2O4、Li x Mn 2-y M yO4, LiMPO4, Li2MPO4F (M; at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). They can be used alone or in combination. From the perspective of achieving a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO2、Li x Co y Ni 1-y O2、Li x Ni 1-y M y O z Lithium nickel composite oxides such as (M; at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3).

[0047] Examples of the conductive agent include carbon black (CB), acetylene black (AB), Ketjen black, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0048] Examples of the binder include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, and polyolefin-based resins, etc. These may be used alone or in combination of two or more.

[0049] [Spacer]

[0050] The spacer 13 may be made of, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, and the like. Suitable materials for the spacer include olefin resins such as polyethylene and polypropylene, and cellulose. The spacer 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, a multilayer spacer including a polyethylene layer and a polypropylene layer may be used, and a spacer 13 having a surface coated with an aramid resin, ceramic, or the like may be used.

[0051] [Non-aqueous electrolyte]

[0052] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt that is a solvent in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolyte) and can be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent can use, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen substituted product formed by replacing at least a portion of the hydrogen of these solvents with a halogen atom such as fluorine.

[0053] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0054] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ether, 1,2-dimethoxyethane, ethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether. , butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.

[0055] As the halogen-substituted product, fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as methyl fluoropropionate (FMP), and the like are preferably used.

[0056] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic carboxylic acid lithium, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 21+1 SO2)(C m F 2m+1 SO2) {1, m is an integer greater than 1} and other imide salts. The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoint of ion conductivity, electrochemical stability, etc. The concentration of the lithium salt is preferably set to 0.8 to 1.8 mol per 1 L of solvent.

[0057] Example

[0058] Hereinafter, the present application will be further described by way of examples, but the present application is not limited to these examples.

[0059] <Example 1>

[0060] [Production of positive electrode]

[0061] As the positive electrode active material, lithium cobalt oxide (LiCo) containing zirconium, magnesium and aluminum is used. 0.979 Zr 0.001 Mg 0.01 Al 0.01 O2). The positive electrode active material is mixed in an amount of 95 parts by mass, the carbon powder as a conductive agent is mixed in an amount of 2.5 parts by mass, and the polyvinylidene fluoride powder as a binder is mixed in an amount of 2.5 parts by mass, and then an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added to prepare a positive electrode mixture slurry. The slurry is applied to both sides of a positive electrode collector formed of aluminum foil (thickness 15 μm) by a doctor blade method, and after the coating is dried, the coating is rolled by a calendering roller to prepare a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode collector.

[0062] [Preparation of Carbon Material A]

[0063] The coke was crushed to an average particle size of 13 μm, and pitch was added as a binder to the crushed coke, and the mixture was pressed to form a block. The block was calcined at a temperature of 2500°C or higher to graphitize it, and then the block was crushed and sieved using a 250-mesh sieve to obtain a carbon material A having an average particle size of 23 μm. The true density of the prepared carbon material A was 2.2 g / cm based on the result of the pycnometer method. 3 .

[0064] [Preparation of Carbon Material B]

[0065] The coke was crushed to an average particle size of 13 μm, and pitch was added as a binder to the crushed coke to aggregate the coke to an average particle size of 18 μm. The aggregate was calcined at 1000°C and sieved with a 250-mesh sieve to obtain a carbon material B with an average particle size of 18 μm. The true density of the prepared carbon material B was 1.7 g / cm based on the result of the pycnometer method. 3 .

[0066] [Production of negative electrode]

[0067] Carbon material A was mixed in such a manner that it became 94 parts by mass and SiO became 6 parts by mass, and this was used as negative electrode active material A. Negative electrode active material A: Na salt of carboxymethyl cellulose (CMC-Na): styrene-butadiene copolymer rubber (SBR) were mixed in such a manner that the mass ratio became 100:1:1, and the mixture was kneaded in water to prepare the first negative electrode mixture slurry. In addition, carbon material B was mixed in such a manner that it became 94 parts by mass and SiO became 6 parts by mass, and this was used as negative electrode active material B. Negative electrode active material B: CMC-Na: SBR were mixed in such a manner that the mass ratio became 100:1:1, and the mixture was kneaded in water to prepare the second negative electrode mixture slurry.

[0068] The first negative electrode mixture slurry is applied to both sides of the negative electrode collector formed by copper foil by a doctor blade method to form a first negative electrode mixture layer. Furthermore, the second negative electrode mixture slurry is applied on the first negative electrode mixture layer to form a second negative electrode mixture layer. At this time, the coating mass ratio per unit area of ​​the first negative electrode mixture slurry and the second negative electrode mixture slurry is set to 10:90. After the first negative electrode mixture layer and the second negative electrode mixture layer are dried, they are rolled using a calendering roller to produce a negative electrode. It should be noted that the coating amount of the slurry in the positive electrode and the negative electrode is adjusted in such a way that the ratio of the negative electrode charge capacity at 4.2V to the positive electrode charge capacity, that is, the charge capacity ratio (negative electrode charge capacity / positive electrode charge capacity) becomes 1.1.

[0069] [Preparation of non-aqueous electrolyte]

[0070] LiPF6 was dissolved at a concentration of 1.0 mol / L in a non-aqueous solvent prepared by mixing ethylene carbonate (EC), propylene carbonate (PC) and ethyl methyl carbonate (EMC) in a volume ratio of 10:10:80 to prepare a non-aqueous electrolyte.

[0071] [Fabrication of non-aqueous electrolyte secondary battery]

[0072] (1) The positive electrode lead is mounted on the positive electrode collector, the negative electrode lead is mounted on the negative electrode collector, and then the positive electrode and the negative electrode are wound with a separator formed of a polyethylene microporous film between them, and a polypropylene tape is attached to the outermost circumference to prepare a cylindrical electrode body. Then, the electrode body is pressed to prepare a flat electrode body.

[0073] (2) Prepare a sheet-like laminated material formed by a 5-layer structure of resin layer (polypropylene) / adhesive layer / aluminum alloy layer / adhesive layer / resin layer (polypropylene), set a cup-shaped storage portion for storing the electrode body in the laminated material, and fold the laminated material back in a manner covering the storage portion to form a bag-shaped outer body. In a glove box under an argon atmosphere, insert the flat electrode body and the non-aqueous electrolyte into the storage portion of the outer body. Then, the interior of the outer body is depressurized so that the non-aqueous electrolyte is impregnated into the interior of the separator, and the open end of the outer body is sealed to produce a bag-type non-aqueous electrolyte secondary battery with a height of 62 mm, a width of 35 mm, and a thickness of 3.6 mm.

[0074] <Examples 2, 4, Comparative Examples 5 to 7>

[0075] As shown in Table 1, a nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that the mass ratio of the first negative electrode mixture layer to the second negative electrode mixture layer was changed.

[0076] <Example 3>

[0077] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 2 except that the negative electrode active material B was replaced with the negative electrode active material C produced by mixing the carbon material C produced as follows and SiO.

[0078] [Production of Carbon Material C]

[0079] The coke was crushed to an average particle size of 13 μm, and pitch was added as a binder to the crushed coke to aggregate the coke to an average particle size of 18 μm. The aggregate was calcined at 1050°C and sieved with a 250-mesh sieve to obtain a carbon material C with an average particle size of 18 μm. The true density of the prepared carbon material C was 1.9 g / cm based on the result of the pycnometer method. 3 .

[0080] <Comparative Examples 1 to 4>

[0081] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that a single negative electrode mixture layer containing the negative electrode active material shown in Table 1 was used instead of the two negative electrode mixture layers.

[0082] [Calculation of interparticle void ratio of carbon material]

[0083] At an ambient temperature of 25°C, the non-aqueous electrolyte secondary batteries of each embodiment and each comparative example were charged at a constant current of 0.2C (920mA) to 4.2V, and then charged at a constant voltage of 4.2V to C / 50. Then, they were discharged at a constant current of 0.5C to 2.5V. The charge and discharge was set as 1 cycle, and 5 cycles were performed. The negative electrode was taken out from the non-aqueous electrolyte secondary batteries of each embodiment and each comparative example after 5 cycles, and the interparticle porosity of the carbon material was compared between the first negative electrode mixture layer and the second negative electrode mixture layer. As a result, Examples 1 to 4 and Comparative Examples 5 to 7 all confirmed that the interparticle porosity of the second carbon material in the second negative electrode mixture layer was greater than the interparticle porosity of the first carbon material in the first negative electrode mixture layer. It should be noted that for Comparative Examples 1 to 4, the interparticle porosity of the carbon material was not measured.

[0084] [Determination of liquid absorption time]

[0085] The negative electrode of the embodiment and the comparative example was dried for 10 hours in a constant temperature bath heated to 200°C under a nitrogen atmosphere, and each negative electrode was cut into a size of 2cm×5cm to make a sample. 3μL of polypropylene carbonate (PC) was dripped vertically on the surface of each sample, and the time until PC was absorbed into the interior of the sample was visually measured. Each sample was measured 6 times, and the average value was taken as the absorption time. It should be noted that the shorter the absorption time, the better the permeability of the electrolyte to the negative electrode.

[0086] [Measurement of battery capacity and discharge load characteristics]

[0087] At an ambient temperature of 25°C, the non-aqueous electrolyte secondary batteries of the embodiments and comparative examples are charged to 4.2V at a constant current of 1C (800mA), and then charged to 1 / 50C at a constant voltage of 4.2V. Then, 1C (800mA) is used for constant current discharge to 2.75V, and the discharge capacity at this time is set to 1C discharge capacity. In addition, after constant current charging to 4.2V is performed in the same manner, constant voltage charging is performed to 1 / 50C at 4.2V, and then, 3C (2400mA) is used for constant current discharge to 2.75V, and the discharge capacity at this time is set to 3C discharge capacity. The discharge load characteristics of the non-aqueous electrolyte secondary batteries of the embodiments and comparative examples are obtained by the following formula. It should be noted that the higher the discharge load characteristics, the better the discharge characteristics. In addition, the 1C discharge capacity is set to the battery capacity.

[0088] Discharge load characteristics = (3C discharge capacity / 1C discharge capacity) × 100

[0089] Table 1 summarizes the results of electrolyte permeability, discharge load characteristics, and battery capacity of the non-aqueous electrolyte secondary batteries of the embodiments and comparative examples. In Table 1, the values ​​of the liquid absorption time, discharge load characteristics, and battery capacity of Comparative Example 1 are set to 100, and the values ​​of other embodiments and comparative examples are shown as relative values. In addition, Table 1 also shows the types and mass ratios of the negative electrode active materials of the first negative electrode mixture layer and the second negative electrode mixture layer.

[0090] [Table 1]

[0091]

[0092] Compared with Comparative Example 1, although the discharge load characteristics of Comparative Example 2 are improved, the battery capacity is greatly reduced. This result suggests that when the negative electrode active material B is used, although the battery capacity is reduced, the discharge load characteristics are improved. However, in Comparative Examples 3 and 4 using a mixture of negative electrode active material A and negative electrode active material B, compared with Comparative Example 2, although the reduction in battery capacity is suppressed, the improvement effect of the discharge load characteristics is not sufficient. Therefore, when the mixture of negative electrode active material A and negative electrode active material B is used within the range in which the reduction in battery capacity is suppressed, the discharge load characteristics cannot be fully improved. In contrast, Examples 1 to 4 suppress the reduction in battery capacity in the same way as Comparative Examples 3 and 4, and show discharge load characteristics that are equal to or higher than those of Comparative Example 2. Therefore, by using a two-layer negative electrode mixture layer that meets the specified conditions, a non-aqueous electrolyte secondary battery with high capacity and good rapid charge and discharge characteristics can be achieved.

[0093] Description of Reference Numerals

[0094] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 outer body, 16 sealing body, 17, 18 insulating plates, 19 positive electrode lead, 20 negative electrode lead, 21 groove portion, 22 filter, 23 lower valve body, 24 insulating member, 25 upper valve body, 26 cover, 26a opening portion, 27 gasket, 30 negative electrode collector, 32 negative electrode mixture layer, 32a first negative electrode mixture layer, 32b second negative electrode mixture layer.

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising: a negative electrode current collector, a first negative electrode mixture layer provided on a surface of the negative electrode current collector, and a second negative electrode mixture layer provided on a surface of the first negative electrode mixture layer, The first negative electrode mixture layer includes, as a negative electrode active material, 3 ~2.3g / cm 3 The No. 1 carbon material, The second negative electrode mixture layer includes, as a negative electrode active material, a 3 And at 2.0g / cm 3 The following second carbon material, The interparticle porosity of the second carbon material in the second negative electrode mixture layer is greater than the interparticle porosity of the first carbon material in the first negative electrode mixture layer. The mass ratio of the first negative electrode mixture layer to the second negative electrode mixture layer is 95:5 to 80:

20.

2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein At least one of the first negative electrode mixture layer and the second negative electrode mixture layer contains a Si-based material.

3. A non-aqueous electrolyte secondary battery comprising: The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, Positive electrode, and Non-aqueous electrolytes.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP1995192724A

  • Lithium secondary battery

    JP1999250936A

  • Negative electrode, and non-aqueous electrolyte secondary battery using the same

    CN101202338A

  • Negative-electrode material for nonaqueous-electrolyte secondary battery, negative-electrode mixture for nonaqueous-electrolyte secondary battery, negative electrode for nonaqueous-electrolyte secondary battery, nonaqueous-electrolyte secondary battery, and vehicle

    CN106165161A

  • Negative electrode for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

    CN106797020A